Comparative Study on the Effect of Ultrasonic Power on the Microstructure and Mechanical Properties of 2195 Aluminum Alloy Ingot - Hu, Yuqi; Jiang, Ripeng; Li, Xiaoqian (Frontiers in Materials, 2022)
High-intensity ultrasound was introduced during the casting of 2195 aluminum-lithium alloy ingots. The size of the ingots is a cylinder with a length of 650 mm and a radius of 30 mm.. The effects of different ultrasonic power applied in the melt on the grain shape, a-Al grain size, the size of the precipitated phase and the mechanical properties of the ingot were compared. The results show that when the total real-time power of the ultrasonic system is maintained at 1600W, an ingot with a more uniformly dispersed precipitation phase grain refinement structure is obtained. At the same time, the mechanical performance of the ingot reaches its peak under the same power state. Analyzing the reasons, it is concluded that under the power state of 1600W, the coarse eutectic structure in the ingot is controlled most effectively, and the performance of the ingot reaches the highest value.